EFFECTS OF VARIOUS GROUND ANGLE ON SHOULDER MUSCLE ACTIVITY DUR- ING SHOULDER PROTRACTION EXER- CISE - Gu, Qian (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to examine differences in surface electromyography (EMG) activ- ities in upper trapezius, pectoralis major, and serratus anterior muscles during shoulder protraction exercise with various ground angle. The research subjects included 16 healthy participants (M=10, F=6) who volunteered.All subjects were measured EMG activities in the serratus anterior, upper trapezius, and pectoralis major during performance of shoulder protraction exercise on a surface at 0° tilt, 30° tilt, 60° tilt, and 90° tilt, respectively. Statistical analysis was performed one-way analysis of variance (ANOVA). There was significant difference in theserratus anterior (ｐ＜0.05). The results of post-hoc analysis showed significantly greater value of serratus ante- rior on a surface at a 0° tilt angle than at 60° and 90° tilt angles (ｐ＜0.05). This study suggest that performanceof shoulder protraction exercise on the 0°angled ground can be regarded as the best choice to strengthen the serratus anterior with healthy adults.